KONTRIBUSI MINAT BELAJAR DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SENI RUPA DI SMPN 2 PADANG - YOZI PUTRI, Drs. Yusron Wikarya, M.Pd., Dr. Yahya, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of this study are (1) the contribution of learning interest to thelearning outcomes, (2) the contribution of students' creativity to the learningoutcomes, (3) the contribution of learning interest and creativity of studentstogether to the learning result of Visual Arts in SMPN 2 Padang. The type ofresearch is correlational descriptive. The study population was 848 studentsand the sample was 96 students. Questionnaire is tested for its validity andreliability. Data analysis using simple correlation and double correlationtechniques. The result of the research are (1) positive and significantcontribution between learning interest toward learning result 10,50%, (2)positive and significant contribution between student creativity towardlearning result 21,81%, (3) positive contribution and significant betweenlearning interest and creativity of student together to result of learning equalto 22,10%.Kata kunci: minat belajar, kreativitas siswa, hasil belajar Seni Rupa